Standardized Assessment of Substance-Related, Other Psychiatric, and Comorbid Disorders among Probationers - Swartz, James A.; Johnson, Timothy P.; Graf, Ingrid; Pickup, Lillian (International journal of offender therapy and comparative criminology, 2003)
Diagnostic and Statistical Manual of Mental Disorders